1983
DOI: 10.1128/iai.42.2.531-538.1983
|View full text |Cite
|
Sign up to set email alerts
|

Study of heart-reactive antibody in antisera and hybridoma culture fluids against group A streptococci

Abstract: Heart-reactive antibody is known to be produced in animals immunized with group A streptococci. However, the detection and quantitation of these antibodies and their respective antigens have been limited to immunofluorescence or immunoprecipitation tests. In this study a more sensitive technique was used to detect heart-reactive antibody, i.e., the enzyme-linked immunosorbent assay (ELISA). Countercurrent immunoelectrophoresis and agar gel immunodiffusion were also used to confirm the reactivity of rabbit anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The heavy chain V region (VH) and Vx sequences of nine of these IgMX tLF were determined at the cDNA level. Five VH genes in three V. families were used by these antibodies (Ab), including V.I (dp21/1-4b and dpl0 [51pl]/ hv1051), V.3 (dp38/3-15 and dp77/ [13][14][15][16][17][18][19][20][21], and V.4 (dp70/4-4b). The deduced V gene-encoded amino acid sequences of the X chains of these IgMX tLF confirmed their serological classification as xlII, and they were further classified as members of the relatively uncommon VxlII subgroup, designated VxlIIb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heavy chain V region (VH) and Vx sequences of nine of these IgMX tLF were determined at the cDNA level. Five VH genes in three V. families were used by these antibodies (Ab), including V.I (dp21/1-4b and dpl0 [51pl]/ hv1051), V.3 (dp38/3-15 and dp77/ [13][14][15][16][17][18][19][20][21], and V.4 (dp70/4-4b). The deduced V gene-encoded amino acid sequences of the X chains of these IgMX tLF confirmed their serological classification as xlII, and they were further classified as members of the relatively uncommon VxlII subgroup, designated VxlIIb.…”
Section: Discussionmentioning
confidence: 99%
“…The Vx-subgroup nature of the h-type IgM anti-rabbit IgG RF was determined by ELISA using murine mAbs specific for the VxI, VxII, VxIV, and VxVI subgroups and the VxIIIa, VxIIIb, and VxIIIc sub-subgroups (19). The ELISA for KF-binding to streptococcal extract was kindly performed by Dr. Madeleine W. Cunningham (University of Oklahoma, Oklahoma City, OK) (20). The affinity constants of R.F to rabbit IgG and myosin were measured by ELISA as described by Friguet et al (21).…”
Section: Methodsmentioning
confidence: 99%
“…Nine proteins could be characterized either by amino acid sequencing (spot nos. 1,7,8,9,10,11) or by MoAbs (spot nos. 2, 3, 5) ( Table 1).…”
Section: Sequence Analysis Of Immunostained Antigensmentioning
confidence: 99%
“…Other cross-reactive proteins of the myocardial tissue have not yet been identified by their protein sequence but only by their molecular weight. Cunnigham & Russel [11] demonstrated that autoreactive antibodies from sera of patients with RHD bind, in one-dimensional Western blot analysis, to heart tissue proteins with molecular masses 40, 67 and 200 kD. In subsequent studies, myosin has been identified as the relevant 200-kD protein immune target in myocardial tissue [12].…”
Section: Introductionmentioning
confidence: 99%
“…Monoclonal Antibodies. Murine hybridoma cell lines were selected, cloned, stored and maintained as previously described (20). mAbs used in this study included 36.2.2, 49 .8 .9, and 54 .2 .8, which were stored as culture fluids at 4°C .…”
Section: Methodsmentioning
confidence: 99%